2007
DOI: 10.1016/j.bbmt.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir Inhibits Lymphocyte Proliferation by Impairing DNA Synthesis

Abstract: Cytomegalovirus (CMV) disease-related mortality in allogeneic hematopoietic stem cell transplant (HSCT) recipients has dramatically declined because of ganciclovir prophylaxis and preemptive therapeutic strategies. However, ganciclovir has not improved overall survival in randomized studies despite effectively preventing overt CMV disease. Moreover, recurrent posttransplant CMV antigenemia, associated with prolonged ganciclovir exposure, is a predictor of increased relapse of malignancy. We examined the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 24 publications
7
54
0
Order By: Relevance
“…Unlike acyclovir, ganciclovir inhibits lymphocyte functions in healthy volunteers (32). In healthy volunteers, ganciclovir has been shown to suppress lymphocyte proliferation and activation by inhibiting DNA synthesis (33). Although in an analysis of lymphocyte function in a subgroup of the 2VAL Study, valganciclovir was shown to reduce lymphocyte proliferation and activated T-cell count, this effect was not documented with valacyclovir (34).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike acyclovir, ganciclovir inhibits lymphocyte functions in healthy volunteers (32). In healthy volunteers, ganciclovir has been shown to suppress lymphocyte proliferation and activation by inhibiting DNA synthesis (33). Although in an analysis of lymphocyte function in a subgroup of the 2VAL Study, valganciclovir was shown to reduce lymphocyte proliferation and activated T-cell count, this effect was not documented with valacyclovir (34).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the therapy of CMV reactivation (such as ganciclovir) can suppress T-lymphocyte proliferation which may translate into impaired immune reconstitution after HSCT. 26 Thus, CMV reactivation may be associated with PTLD after haplo-HSCT.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, preemptive treatment of CMV uses costly antiviral agents which incur toxicities such as renal damage and cytopenia, requiring further treatment and hospitalizations (7, 15). The use of ganciclovir enhances immunosuppression in vitro (16) and multiple episodes of CMV reactivation are associated with late relapse and treatment failure (17). Prevention of CMV reactivation rather than its preemptive management may be advantageous by avoiding toxicity from antiviral treatment and reducing the economic burden of post-transplant care.…”
Section: Introductionmentioning
confidence: 99%